Traumatic Brain Injury Patients in the Emergency Unit of a Tertiary Hospital - Ramdinal Aviesena Zairinal; Chandrika Najwa Malufti; Yetty Ramli; Diatri Nari Lastri; Adre Mayza; Pukovisa Prawiroharjo (Folia Medica Indonesiana, 2023)
Highlights: